Fractional-order harmonics in the trajectory control of redundant manipulators - Duarte, Fernando B. M. (2019)
Redundant manipulators are superior to classical arms because they allow the trajectory optimization, the obstacle avoidance, and the resolution of singularities. For this type of manipulators, the kinematic control algorithms adopt generalized inverse matrices that may lead to unpredictable responses. Motivated by these problems this paper studies the complexity revealed by the trajectory planning scheme when controlling redundant manipulators. The result reveals a chaotic phenomenon and the existence of fractional order sub-harmonics in the robot signals.